Efektivitas Metode Pembelajaran Gasing terhadap Hasil Belajar Matematika Materi Bangun Ruang Kelas VI SDN 173420 Pollung - Agnes Agustina Gultom; Khairul Usman (Institut Nalanda, 2024)
This study aims to determine the effectiveness of the Gasing learning method on mathematics learning outcomes of class VI spatial building materials of SDN 173420 Pollung T.A 2023/2024. This research is an experimental study with an experimental approach. The sample used in this study was 27 grade VI students. The research instruments consisted of (1) Interview sheets related to mathematics learning outcomes, and (2) test instruments in the form of questions to determine student learning outcomes. The data analysis technique was carried out descriptively and continued with the N-Gain test to test the level of effectiveness of the learning method.Based on the statistical descriptive data analysis, the average pre-test score was 45.7 and the post-test score was 80.5. Then in the hypothesis test through the N-Gain test with an effectiveness level of 70%, it can be concluded that the Gasing learning method is quite effective on the learning outcomes of mathematics in the material of spatial structures of class VI. From the explanation above, Ho is rejected and Ha is accepted, meaning: The effectiveness of the Gasing learning method on the learning outcomes of mathematics in the material of spatial structures of class VI SDN 173420 Pollung T.A 2023/2024.